Balancing cultures: Acculturation, environmental mastery, emotional regulation, and depressive symptoms among first-generation Latino/a youth. Issue 3 (3rd May 2016) - Archuleta, Adrian J.; Lakhwani, Monica
ABSTRACT: The rate of growth of Latino populations in some communities exceeds the resources available to assist Latino families in adapting to new environments. Some risk factors for depression center on their acculturative experiences; however, it is often unclear under what circumstances these experiences become stressful. Moreover, it is often unclear which protective factors should be given priority in developing interventions that reduce depressive symptoms in this context. The current study examines the relationship between acculturation, emotion regulation, environmental mastery, and depressive symptoms among first-generation Latino youth ( N = 56). It was hypothesized that the interaction between enculturation and acculturation would positively relate to depressive symptoms while emotion regulation would prove to be a stronger protective factor over environmental mastery. The findings support these hypotheses and implications are provided.